Penerapan Smart Governance Dalam Rangka Mewujudkan Desa Tanjung Pasir Kabupaten Tangerang Sebagai Smart Village - Siti Wahyuni Rahmawati; Irvan Arif Kurniawan; Eko Prasetyo (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
In this study, the existence of a smart village in Tanjung Pasir village can understand the problems faced by the village by understanding the latest situation of problems that exist in the village, by managing various resources to be effective and efficient, then by maximizing the purpose of serving the community. This study aims to see how one of the dimensions of a smart village is implemented, namely smart governance in Tanjung Pasir Village, Tangerang Regency. The method used in this study is descriptive qualitative with interview data collection carried out with informants from the Office of the Head of Tanjung Pasir Village and the community. The results of the study show that the implementation of smart governance in order to realize Tanjung Pasir Village as a smart village in the decisions taken by the Tanjung Pasir village government that the Tanjung Pasir village has the right to obtain information through an information system developed by the city government, then from the public and social services side found in Tanjung Pasir Village, namely through the existence of a smart village program that can provide services effectively.